2021
DOI: 10.1007/s13402-021-00647-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the bromodomain and extra-terminal family of epigenetic regulators as a promising therapeutic approach for gastric cancer

Abstract: Purpose Epigenetic dysregulation is a common characteristic of cancers, including gastric cancer (GC), and contributes to cancer development and progression. Although the efficacy of BET (an epigenetic regulator) inhibition has been demonstrated in various cancer types, predictive genetic markers of its efficacy in GC are currently lacking. Therefore, we aimed to identify markers that predict the response of BET inhibition in GC and, suggest an effective treatment regimen through combined therapy. Methods The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…In 2019, Xu et al (28) reported that inhibition of zinc-finger transcription factor 1 (ZEB1) reduced the level of WNT5A in GC, induced apoptosis and inhibited the proliferation and migration of GC cells. Current research on WNT5B is not very clear, although it can predict the sensitivity of the epigenetic regulator BET inhibitor iBET-151 to inhibit the growth of gastric cancer, especially when combined with paclitaxel (29). Therefore, it may be possible to predict the effect of chemotherapy in gastric cancer by WNT5B.…”
Section: Wnt5amentioning
confidence: 99%
See 2 more Smart Citations
“…In 2019, Xu et al (28) reported that inhibition of zinc-finger transcription factor 1 (ZEB1) reduced the level of WNT5A in GC, induced apoptosis and inhibited the proliferation and migration of GC cells. Current research on WNT5B is not very clear, although it can predict the sensitivity of the epigenetic regulator BET inhibitor iBET-151 to inhibit the growth of gastric cancer, especially when combined with paclitaxel (29). Therefore, it may be possible to predict the effect of chemotherapy in gastric cancer by WNT5B.…”
Section: Wnt5amentioning
confidence: 99%
“…b-Catenin responsive transcription inhibitor 3/5 (iCRT3/5), which mainly blocks b-catenin-TCF4 interactions, is in the preclinical stage of gastric cancer treatment, and it can kill gastric cancer malignant cells and inhibit gastric cancer development (88). LF3 is a 4-thioureidobenzenesulfonamide derivative that profoundly inhibits the interaction between b-catenin and TCF4 and reduces the expression of GPX4, inducing iron-induced death in gastric cancer cells (29). In 2018, Wang et al Found that XAV939, a small-molecule inhibitor (SMI), increases degradation of b-catenin by stabilizing Axin and inhibits gastric cancer invasion and metastasis (92).…”
Section: Targeting Wnt Ligands/receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Atherosclerosis [44] Diabetes [45] Fabry disease [12] Chronic kidney disease [46] IBET-762 (GSK-525762) BD1 and BD2 from BRD2,3,4,T Neoplasm [12] Testis carcinoma [47] Midline carcinoma [12] IBET-151 BD1 and BD2 from BRD2,3,4,T MLL-fusion leukemia [48] Colorectal ctumorsancer [42] Gastric cancer [49] Vismodegib-resistant esophageal adenocarcinoma [50] Rheumatoid arthritis [15] Melanoma [51] Myeloma [52] MK8628/OTXO15 BRD2,3,4…”
Section: Overview Of Bet Bromodomainmentioning
confidence: 99%
“…Inhibition of BRD4 has been reported to suppress GC progression and metastasis by destabilizing snail family transcriptional repressor 1 (SNAIL) or downregulating c-myc expression [ 5 , 6 ]. BET bromodomain inhibitors, such as iBET-151, ARV-825, and JQ1, are employed in GC in vivo and in vitro and demonstrate effective antitumor activity [ 10 12 ]. Therefore, BRD4 is a promising therapeutic target for GC treatment.…”
Section: Introductionmentioning
confidence: 99%